2005
DOI: 10.1111/j.1467-7652.2005.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐derived mouse IgG monoclonal antibody fused to KDEL endoplasmic reticulum‐retention signal is N‐glycosylated homogeneously throughout the plant with mostly high‐mannose‐type N‐glycans

Abstract: Summaryof the total N -glycans, with Man 7 GlcNAc 2 being the most abundant species. Some complex N -glycans bearing xylose and small amounts of oligosaccharides with both xylose and fucose were identified. No appreciable differences were detected when comparing glycosylation at different leaf ages, e.g. from seedling leaves up to 8 weeks old and top or basal leaves of mature plants, or between leaves, stems and whole plants. A strict retention of glycoproteins to ER by the use of the tetrapeptide KDEL was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
50
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 44 publications
5
50
0
3
Order By: Relevance
“…N-glycans of mammalian glycoproteins produced in transgenic plants differ from their natural forms (Lerouge, 1998). If the transgenic protein is directed toward and retained in the ER, then 80% of the total N-glycans attached to ER-resident proteins in the transgenic plant would be high-mannose-type N-glycans (Helenius and Aevi, 2001;Triguero, 2005). The use of the ER-retention signal has been proposed to restrict glycosylation of plant-derived antibodies or the vaccine to only highmannose-type N-glycans (Triguero, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-glycans of mammalian glycoproteins produced in transgenic plants differ from their natural forms (Lerouge, 1998). If the transgenic protein is directed toward and retained in the ER, then 80% of the total N-glycans attached to ER-resident proteins in the transgenic plant would be high-mannose-type N-glycans (Helenius and Aevi, 2001;Triguero, 2005). The use of the ER-retention signal has been proposed to restrict glycosylation of plant-derived antibodies or the vaccine to only highmannose-type N-glycans (Triguero, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…If the transgenic protein is directed toward and retained in the ER, then 80% of the total N-glycans attached to ER-resident proteins in the transgenic plant would be high-mannose-type N-glycans (Helenius and Aevi, 2001;Triguero, 2005). The use of the ER-retention signal has been proposed to restrict glycosylation of plant-derived antibodies or the vaccine to only highmannose-type N-glycans (Triguero, 2005). However, in this study, the effect of Fc and KDEL on the expression levels and glycosylation patterns could not be investigated since we did not include 5Aβ without Fc or 5Aβ-Fc.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also found that the deficiency of XylT and FucT did not affect the morphology, growth rate, or growth status of tobacco BY2 cells. In previous studies, several strategies have been adopted to minimize the structural differences observed in complex Nglycans of plants and mammals (Palacpac et al, 1999;Triguero et al, 2005). Cox et al reported that RNAi was a valuable tool to eliminate the expression of core α1,3-FucT and β1,2-XylT in the aquatic plant species L. minor (Cox et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…4). The KDEL sequence was incorporated because ER retention is known to increase antibody expression in plants (43); it appeared to be functional, as glycosylation analyses (Table 1) revealed high-mannose modifications consistent with ER localization (10,26,29,51). High mannose content is known to be essential for mediating effector function (54).…”
Section: Discussionmentioning
confidence: 99%
“…Plant glycosylations differ from mammalian glycosylations in both sugar content and pattern, as they lack sialylations (47) and residues, such as ␤(1,4)-Gal and ␣(2,6)-NeuAc, that are often found on mammalian glycans (17,19). MAbs expressed in transgenic tobacco plants are typically glycosylated with highmannose carbohydrates (10,17,29,48,51); thus, a major concern regarding plant-produced MAbs is whether they can support the recruitment of effector functions required for therapeutic efficacy against pathogen targets, such as bacteria.…”
mentioning
confidence: 99%